2022
DOI: 10.1039/d1an01951a
|View full text |Cite
|
Sign up to set email alerts
|

The transfer and persistence of metals in latent fingermarks

Abstract: In forensic science, knowledge and understanding of material transfer and persistence is inherent to the interpretation of trace evidence and can provide vital information on the activity level surrounding a...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…To visualize metal ions in latent FMs with a spatial resolution at the micron level, Boseley et al demonstrated the capability of synchrotron-sourced X-ray fluorescence microscopy and IR microspectroscopy. 262 This allowed them to determine the distribution of metal ions in FM samples. It was determined that metal content can be easily transferred to and removed from FMs.…”
Section: ■ Physics/pattern Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…To visualize metal ions in latent FMs with a spatial resolution at the micron level, Boseley et al demonstrated the capability of synchrotron-sourced X-ray fluorescence microscopy and IR microspectroscopy. 262 This allowed them to determine the distribution of metal ions in FM samples. It was determined that metal content can be easily transferred to and removed from FMs.…”
Section: ■ Physics/pattern Interpretationmentioning
confidence: 99%
“…Additionally, this method has endless potential to be used for other forms of trace contamination of FMs: explosives, GSR, cosmetics, etc. To visualize metal ions in latent FMs with a spatial resolution at the micron level, Boseley et al demonstrated the capability of synchrotron-sourced X-ray fluorescence microscopy and IR microspectroscopy . This allowed them to determine the distribution of metal ions in FM samples.…”
Section: Physics/pattern Interpretationmentioning
confidence: 99%
“…Metal traces – The transfer and persistence of metals in fingermarks has been investigated by Boseley et al, using XFM [ 198 ]. Considering different scenarios, the authors showed that the handling of the following items led to an increase of metal traces along the fingermark ridges: (1) for a gun barrel: iron and lead – heterogeneously distributed, (2) for a brass cartridge case: copper, and zinc – homogeneously distributed, (3) for a party sparkler: iron, cobalt, nickel, bromine, and barium.…”
Section: Fingermark Compositionmentioning
confidence: 99%
“…and metals [3], which have been extensively studied. However, there has been little research on the potential of analyzing the amino acid composition in latent fingerprint deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption of over 15 units within 24 h prior to fingerprint deposition resulted in higher proline concentrations in both eccrine-rich and natural fingerprints [11]. MDMA (3,4-methylenedioxy-n-methylamphetamine) inhibits tyrosine hydroxylase activity [12]. MDMA consumption within the past 24 h resulted in 38.5% higher tyrosine levels in fingerprints.…”
Section: Introductionmentioning
confidence: 99%